Antimicrobial Susceptibility of Neisseria gonorrhoeae Isolates in Yaoundé, Cameroon From 2009 to 2014. Issue 12 (December 2018) - Tayimetha, Carolle Y.; Unemo, Magnus
Abstract : Abstract: We investigated the antimicrobial resistance in gonococci 2009 to 2014 in Yaoundé, Cameroon, and recommend revisions of the Cameroonian treatment guideline. We observed a high resistance to ciprofloxacin (17.6%) but no ceftriaxone resistance. Ceftriaxone should replace ciprofloxacin as the recommended first-line treatment for urethral/vaginal discharge. Enhanced resistance surveillance in Africa is essential. Abstract : The gonococcal resistance to first-line treatment for urethral/vaginal discharge, ciprofloxacin, in Cameroon increased from 3.8% to 50.0% during 2009 to 2014. Strengthening of the gonococcal antimicrobial resistance surveillance in Africa is essential.